Islamic cultural and Arabic linguistic influence on the languages of Nusantara; From lexical borrowing to localized Islamic lifestyles - Mahfud, Choirul; Astari, Rika; Kasdi, Abdurrohman; Mu'ammar, Muhammad Arfan; Muyasaroh, Muyasaroh; Wajdi, Firdaus (UI Scholars Hub, 2021)
This article reviews the breadth of the influence of Arabic on the languages of Nusantara, from the early arrival of Islam in the archipelago to the modern era.1 Focusing on both linguistics and culture, we pay attention to precolonial exchanges, regional languages – in particular Bima, Sasak, Javanese, Sundanese, and Bugis – and the recent influence of Arabic and Islamic culture on the development of technological products, Islamic financial systems, and Islamic lifestyles in contemporary Indonesia. From era to era, Arabic has not only played a role in enriching the vocabulary of the languages of Nusantara, it has also contributed to the social, religious, educational, literary, philosophical, legal, political, scientific, and cultural domains.